Pengaruh Peranan Orang Tua Asuh dalam Pembentukan Karakter Anak di Panti Asuhan Putri Aisyiyah Cabang Bukittinggi - Putri, Erlisa; Yarni, Linda (Lembaga Yasin AlSys, 2023)
Children are the fruit of love from both parents who must be given love and affection to fulfill all the needs needed by children. Nowadays there are many children who do not get this, let alone the children who live in the Orphanage Foundation. The children who live in the Orphanage Foundation are not only those who are orphans, orphans or orphans but also those who have complete families but are economically disadvantaged. The aim of the research is to reveal how the role of foster parents is in shaping the character of the children of the Aisyiyah Putri Bukittinggi Orphanage. This research is a qualitative research by analyzing the extent of the role of the orphanage administrators or foster parents in building the character of the children in the orphanage while carrying out PLBKLS at the Aisyiyah Orphanage branch. The results of the study show that children who can be said to still live and have complete parents and families still have bad character, this is caused by the surrounding environment or the character of the child. Meanwhile, foster parents are only tasked with supervising the children's playing environment, providing affection that foster children do not get from biological parents. Foster parents can also set an example for orphans as an effort to build the character of the orphans because foster children will be able to accept that foster parents can be role models and also love apart from just listening to advice. The role of the foster parents themselves is the same as the biological parents of the orphanage children, and this is where the role of the foster parents is indispensable for the development and formation of good character for the children living in the orphanage.